The effect of eight weeks of wrestling and wrestling technique based circuit training on lymphocyte ABCA1 gene expression and plasma apolipoprotein A-I - Rashidlamir, A.; Ghanbari-Niaki, A.; Saadatnia, A. (World Journal of Sport Sciences, 2011)
The aim of the present study was to investigate the associated effect of wrestling and wrestling technique based circuit training on ABCA1 gene expression in lymphocytes. For this purpose, Sixteen well-trained wrestlers (17-22 Yr, 55-75 Kg, 19-25 kg/m2) volunteered and randomly were assigned into training (n = 8) and control (n =8) groups. Experimental group was asked to complete a wrestling technique based circuit training (WTBCT) protocol combined with wrestling training (two sessions/day, morning and evening) for 8 weeks and control group remained sedentary. Blood samples were collected 48 hours before the first session and 48 hours after the last session to measure biochemical variables and to collect lymphocyte for ABCA1 gene expression. Subjects had an overnight fasting. A semi-quantitative technique (RT-PCR) was used for lymphocyte ABCA1 expression. T-student test was employed and data were analyzed by SPSS software (version 16). The results showed no significant differences in pretest ABCA1 gene expression levels, but given training protocol resulted in a higher and significant (P<0.031) ABCA1 gene expression level in training group when compared with control group. Significant increase (P<0.02) and decrease (P<0.004) were observed in plasma HDL-C and LDL-C concentrations respectively and Apo A-I concentration remained unchanged in training group when compared with control group. The present results indicated that WTBCT protocol combined with wrestling training was able to increase lymphocyte ABCA1 expression which was accompanied by higher plasma HDL-C and lower LDL-C concentrations. It seems that in this experimental condition, an anaerobic-based sport combined with WTBCT might be considered as a protocol to stimulate RCT process and cardiovascular improvement and to prevent cardiovascular disease.